The Role of the Mast Cell in Thrombolysis Induced by Heparin and a Heparin-Like Substance SP54 - FitzGerald, D. E (Thrombosis and Haemostasis, 1969)
Mast cell uptake of biologically synthesised sodium heparin S35 was shown by Loomis (4). Selye (7) has reviewed the part played by these cells in the storage and production of heparin-like substances. In the studies preceeding these investigations the thrombolytic action of heparin and SP54 was demonstrated (1). In these experiments it has been shown that following degranulation of the mast cell, intravenously injected heparin or SP54 can be taken up by these cells within 24 hrs.This suggests that the mast cell in the perivascular tissues plays a role in the utilization of injected heparin. It may be that exogenous heparin is altered in some way “in vivo” to produce thrombolysis and that the mast cell plays a part in this mechanism.